A paired metamorphic belt in a subduction‐to‐collision orogen: An example from the South Qilian–North Qaidam orogenic belt, NW China. (21st March 2019) - Li, Xiucai; Niu, Manlan; Yakymchuk, Chris; Wu, Qi; Fu, Changlei
Abstract: The early Palaeozoic South Qilian–North Qaidam orogenic belt in northwestern China records a nearly complete history of early‐stage long‐lived oceanic subduction–accretion followed by late‐stage continental collision. Most previous studies have focused on low d T /d P metamorphism (HP–UHP) in this belt whereas the paired high d T /d P belt in the hinterland has received little attention. In this contribution, phase equilibrium modelling is combined with zircon petrochronology to determine the P–T–t evolution of granulites in the North Wulan gneiss complex in the high d T /d P hinterland of the South Qilian–North Qaidam orogen. Granulites record a clockwise P–T path with near‐peak temperatures of 800–900°C at 5.5–7 kbar. Peak metamorphism was followed by high‐ T decompression. Zircon petrochronology reveals protracted zircon growth from c . 474 to 446 Ma during the high‐ T portion of the P–T path. High d T /d P metamorphism in the North Wulan gneiss complex was likely the result of heat transfer from the underlying hot asthenosphere and minor coeval magmatism in an arc–back‐arc system during slab retreat and roll‐back of the South Qilian oceanic plate. Broadly contemporaneous but slightly younger HP–UHP metamorphism in the foreland of the South Qilian–North Qaidam orogenic belt indicates that the region records an early Palaeozoic paired metamorphic belt. This early Palaeozoic paired metamorphic belt provides a detailed example of dual thermal regimes in a modern‐style orogenic system that can be applied to understanding the time‐scales and P–T conditions of high d T /d P metamorphism that accompany subduction in Phanerozoic and Precambrian orogenic belts.